Partial Encephalocraniocutaneous Lipomatosis Syndrome - Velusamy, S. (J Pediatr Neurosci, 2017)
Encephalocranial lipomatosis is a rare disorder that characteristically involves ectomesodermal tissues such as skin, eye, and the central nervous system. Here, we report a 3-year-old girl presented with developmental delay, seizures, limbal dermoid, and weakness of right lower limb. Imaging revealed hemiatrophy, arachnoid cyst, and polymicrogyria. The constellation of clinical finding and imaging leads to the diagnosis.